SEMANTIC CHARACTERISTICS OF DIFFERENT TYPES OF FORMULAIC EXPRESSIONS - Sheraliyeva Dildora Abduvaxob qizi (PEDAGOGS, 2024)
Abstract: In linguistics, we can explore our knowledge about meaning by studying semantics. Semantics is in linguistics that studying about meaning of words, phrases, sentences, or larger units of discourse. Several disciplines and approaches have contributed to the often contentious field of semantics. One of the crucial questions which unites different approaches to linguistic semantics is that of the relationship between form and meaning. Semantics as a linguistic theory that investigates word meaning. This theory understands that the meaning of a word is fully reflected by its context. For example, proverbs and idioms can be proper samples of analyzing semantically. Proverbs and idioms, as metaphoric expressions or as cultural discourse, are condified on semantic structures. Clearly, proverbs have discursive autonomy and are quoted as “texts”, idioms instead are reproduced as lexical units and they are full of wisdom provide to people, while an idiom is a phrase that has its own meaning. Another difference is that proverbs verbalize general truth and fall back on shared knowledge of the people whereas idioms are fixed phrases with a figurative meaning.